2021
DOI: 10.1002/onco.13853
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of 5-Fluorouracil, Oxaliplatin plus Dasatinib (FOLFOX-D) in First-Line Metastatic Pancreatic Adenocarcinoma

Abstract: Pre-clinical studies have demonstrated that Src inhibition through dasatinib synergistically enhances the anti-tumor effects of oxaliplatin.• In this phase II, single arm study, FOLFOX-D in previously untreated patients with mPC only showed only modest clinical activity, with a PFS of 4 months and OS of 10.6 months. • Continued investigation is ongoing to better understand the role of Src inhibition with concurrent 5-FU and oxaliplatin in a subset of exceptional responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The preceding results suggest that dasatinib could be useful in the treatment of PDAC through inhibition of the SFK/YAP axis. However, clinical trials in patients with PDAC using dasatinib in combination with gemcitabine ( 12 ) or 5-fluorouracil and oxaliplatin ( 14 ) were unsuccessful. We considered that SFK inhibitors not only hinder YAP activation but concomitantly trigger activation of a compensatory pathway(s) that mediates resistance to these drugs ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preceding results suggest that dasatinib could be useful in the treatment of PDAC through inhibition of the SFK/YAP axis. However, clinical trials in patients with PDAC using dasatinib in combination with gemcitabine ( 12 ) or 5-fluorouracil and oxaliplatin ( 14 ) were unsuccessful. We considered that SFK inhibitors not only hinder YAP activation but concomitantly trigger activation of a compensatory pathway(s) that mediates resistance to these drugs ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…An early study demonstrated that administration of the SFK inhibitor dasatinib (10) prevented metastatic dissemination in preclinical models of PDAC but did not interfere with the growth of the primary tumor (11). Subsequent clinical trials in PDAC patients using dasatinib in combination with gemcitabine (12,13) or 5-fluorouracil and oxaliplatin (14) failed to demonstrate significant clinical benefit in PDAC patients. The mechanism(s) leading to dasatinib resistance in PDAC are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…improving from 2016 to 2020, and with a signi cant difference between adjacent years. Icotinib 10 [30] 1.06 0.73 0.22 0.16 Lapatinib 6.8 [31] 0.84 0.57 0.18 0.13 Ge tinib 10 [32] 1.25 0.61 0.27 0.13 Axitinib 12 [33] 2.64 1.89 0.56 0.41…”
Section: Affordabilitymentioning
confidence: 99%
“…Cabozantinib was successfully combined with gemcitabine in a Phase I trial (28) and is currently being studied at more advanced clinical settings (Phase II study in combination with pembrolizumab: NCT05052723). On the other hand, dasatinib has failed in Phase II trials in combination with established protocols (FOLFOX (29) or gemcitabine (30) treatment) to induce remarkable improvements in patient survival. Finally, MAP2K1 is a dual-speci city kinase in the MAP signal transduction pathway, which is involved in growth, adhesion, differentiation among other processes (31), and is targeted by cobimetinib and trametinib (shown here), and solumetinib (see Supplementary Fig.…”
Section: Genes In Driver Pathways Represent Promising Targets For Pha...mentioning
confidence: 99%